Analisis Faktor Rendahnya Kemampuan Perkalian Siswa Mi Al-Ma’arif Kota Sorong - Yuyut Milla (MISOOL: Jurnal Pendidikan Dasar, 2019)
Multiplication is a fundamental mathematical skill that serves as the serves as the foundation for understanding more advanced concepts such as division and fractions. However, the evaluation results in class IV B of MI Al-Ma’arif Kota Sorong show that many students still experience difficulties in mastering multiplication operations. This study aims to analyze the factors cousing the low multiplication operations. This study aims to analyze the factors causing the low multiplication ability among students. The research employed a qualitative approach with a case study design. Data were collected through observation, open-ended questionnaires, and documentation, and analyzed using thematic analysis techniques. The findings revealed that internal factors influencing students’ difficulties include weak conceptual understanding, limitedcomputational skills, low motivation, and lack of self-confidence. External factors of suboptimal use of learning media, less varied teaching strategies, and minimal parental support at home. The teacher has made efforts to improve learning outcomes through the use of concrete media and interactive learning, although their effectiveness still needs enhancement. Therefore, improving students’ multiplication skills requires collaboration among teacher, students, and parents to crate meaningful and engaging learning experiences.